Bingkai Media Lokal Kalimantan Timur Terhadap Pemindahan Ibu Kota Negara (IKN) - Noviananda, Dhandy; Hasfi, Nurul; Nugroho, Adi (Interaksi Online, 2024)
The relocation of the National Capital has become a topic of discussion for the Indonesian people, where the relocation of IKN is a topic that is very rarely discussed because of the statement made by Indonesian President Joko Widodo which will move the Indonesian National Capital from DKI Jakarta to East Kalimantan Island, more specifically North Penajam Paser. . From the statement of the President of the Republic of Indonesia, the public has an opinion regarding the relocation of the country's capital, which is DKI Jakarta. The national media has an opinion based on how they report on the relocation of IKN. There are those who support it, there are also those who reject it. This research will discuss the attitude of the local East Kalimantan media regarding the statement regarding the relocation of IKN. By using framing analysis, Zhongdang Pan and Gerald M Kosicki. Researchers selected and analyzed 10 news stories from local media Tribunkaltim which were the research subjects, namely Tribunkaltim with a news period of 1-30 March 2022. The results of this research found that the local online media tribunkalitm used 3 themes in reporting on the relocation of the National Capital, namely: (1) Society (2) Potential Natural Disasters (3) Government preparations that were not optimal. These 3 themes show the framing that rejects the relocation of IKN. Tribunkaltim was seen using local community sources for the content of Tribun Kaltim's news where the community was worried about the relocation of IKN which was placed in North Penajam Paser. Tribun Kaltim also expressed its rejection on the grounds that the IKN buffer villages have the potential for natural disasters and reported that preparations for the IKN relocation were not optimal in terms of preparation. In this case, Tribunkaltim applies framing of a topic or event in society for the needs of society or the media itself. Tribunkaltim framed the relocation of IKN as not providing benefits to the community and also lacking thorough preparation in planning the relocation. The framing carried out by Tribunkaltim shows the media's attitude towards the relocation of IKN promoted by the government by rejecting it by framing the Community. and also shows how the government has less than optimal preparations in preparing for the relocation of IKN.